Immersive Virtual Reality for Patient Education in Orthodontics: Cross-Sectional Feasibility and Acceptability Study - Yoo Jin Kim; Glenn Jou; Hyun Cho; Mathias Stephen Fallis; Glenn Sameshima (JMIR Serious Games, 2026)
Abstract Background Patient education is central to orthodontic care; however, most patients still learn about their malocclusion from conventional records, such as 2D image records. Immersive virtual reality (VR) allows patients to view and manipulate 3D dental models in a head-tracked environment, as part of the serious-games and extended reality family for health education. Evidence on patient-facing immersive VR in orthodontics remains limited, as most dental VR work has addressed student training rather than patient education. Objective This feasibility study aimed to evaluate acceptance, perceived educational value, self-rated experience, ease of use, and self-reported preference regarding an immersive VR consultation room among patients undergoing orthodontic treatment. Methods This cross-sectional, single-arm feasibility and acceptability study was conducted in a university orthodontic clinic between August and September 2024. Patients undergoing active orthodontic treatment completed a single, approximately 15-minute immersive VR educational experience using a Meta Quest 3 headset and a Unity3D-developed consultation room presenting a 3D rendering of each participant’s own intraoral scan, followed by an investigator-developed postexperience questionnaire. The questionnaire combined a Likert scale and two 10-point numeric items with open-ended prompts. Closed-ended responses were summarized as counts, percentages, and 95% CIs, and numeric items were summarized as means with 95% CIs; open-ended comments were grouped into themes. No inferential testing was performed. Results Twenty-eight patients completed the study (mean age 21.6, SD 4.3, range 13‐33 y; 18 males, 10 females; 5 minors). Sixteen (57%) patients had no prior VR experience, 22 (79%) were interested in using VR to learn about their teeth, and 24 (86%) agreed that VR could help patients understand their teeth and braces. The mean overall experience rating was 7.9 (SD 1.6; 95% CI 7.3‐8.5) on a 10-point scale, and the mean ease-of-use rating was 6.6 (SD 2.6; 95% CI 5.7‐7.6). Twenty (71%; 95% Wilson score CI 53‐85) patients felt VR was a better learning modality than conventional 2D images; 19 (68%; 95% Wilson score CI 49‐82) preferred VR with the current setup, and 25 (89%; 95% Wilson score CI 73‐96) preferred VR under a hypothetically improved technology scenario. Positive comments emphasized interactivity, 3D visualization, and engagement; negative comments centered on controller difficulty, latency, and motion discomfort. Two (7%) patients reported mild, transient, motion-related discomfort; none discontinued. Conclusions Patients were generally receptive to an immersive VR consultation room. This work is novel in evaluating patient-facing immersive VR using each patient’s own intraoral scan and in identifying actionable usability and motion-comfort barriers. Because the design was single arm and the comparison with conventional 2D image records was self-reported, the findings represent preliminary acceptability evidence, not learning effectiveness. If confirmed in more rigorous studies, immersive VR may serve as an adjunct to communication with patients undergoing orthodontic treatment, warranting controlled studies with an interactive flat-screen 3D comparator; validated usability, presence, and cybersickness instruments; and objective knowledge-gain measures.